Smart Access Control System for High Security Buildings Using VNPR Technology (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents the development and implementation of a smart access control system designed to enhance security in high-security buildings. The system leverages Vehicle Number Plate Recognition (VNPR) technology, utilizing a Raspberry Pi, Pi camera, and servo motors for automated access control. The Pi camera captures images of vehicles approaching the building, and advanced ANPR algorithms process these images to extract the license plate information. This extracted data is then compared against a centralized database of authorized license plates. Upon successful match, the system automatically triggers a servo motor to control the building's barrier, granting access to the authorized vehicle. The system also provides real-time alerts for unauthorized access attempts, further bolstering security. This scalable solution offers a robust and efficient access control mechanism suitable for various high-security facilities, ensuring only authorized vehicles gain entry.
Keywords: Access Control; Security; VNPR (Vehicle Number Plate Recognition); ANPR (Automatic Number Plate Recognition); Raspberry Pi; Pi Camera; Servo Motor